Supplemental oxygen did not significantly affect two-year mortality in patients at-risk for cardiovascular complications undergoing moderate- to high-risk abdominal surgery–A follow-up analysis of a prospective randomized clinical trial - Taschner, Alexander; Fleischmann, Edith; Kabon, Barbara; Falkner von Sonnenburg, Markus; Adamowitsch, Nikolas; Horvath, Katharina; Christian, Thomas; Emler, David; Fraunschiel, Melanie; Graf, Alexandra; Reiterer, Christian (Frontiers in Anesthesiology, 2023)
Background In relatively healthy middle-aged patients, recent studies have shown that supplemental oxygen did not significantly increase one-year mortality after noncardiac surgery. If supplemental oxygen influences long-term mortality, specifically in elderly patients with cardiovascular risk-factors, remains unknown. Thus, we evaluated the effect of supplemental oxygen on two-year mortality in patients with cardiovascular risk factors undergoing moderate- to high-risk major abdominal surgery. Methods This is a follow-up study of a prospective, randomized, double-blinded, clinical trial. Two hundred fifty-eight patients, who were at least 45 years of age and at-risk for cardiovascular complications were randomly assigned to receive 80 vs. 30% oxygen during surgery and for the first two postoperative hours. Vital status was obtained from all patients 2 years after surgery using the national registry. Preoperative and postoperative maximum concentrations of NT-proBNP, Troponin T (TnT), Copeptin, von Willebrand Factor (vWF), static oxidation-reduction potential (sORP) and oxidation-reduction potential capacity (cORP) were tested for association with two-year mortality. Results The median age of patients was 74 years (25th-75th percentile 70–78 years). 25.8% (95% CI: 17.3–32.4%) of patients in the 80% oxygen group and 22.3% (95% CI: 14.8–29.1%) in the 30% oxygen group died within 2 years after surgery. No significant difference in two-year mortality was found between patients, who received 80% oxygen concentration, versus patients, who received 30% oxygen concentration (estimated hazard ratio 1.145; 95% CI 0.693–1.893; p = 0.597). Preoperative Copeptin concentrations and postoperative maximum vWF activity were significantly associated with two-year mortality (p < 0.001). Conclusion Our results are consistent with previous studies, that showed that supplemental oxygen did not increase long-term mortality. Therefore, it is becoming more evident that supplemental oxygen may not have a significant effect on long-term outcome in patients undergoing major abdominal surgery.